Dismantling the Stereotype: A Perspective on PINK - Naveena V. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Films are one of the major sources of entertainment for people in India as elsewhere across the globe. Films of any country mirror its culture, tradition, hopes, aspirations of people besides lot many other factors. In to1tality, films could be termed as the cultural consciousness of a nation. However, sometimes, among these stereotypical portrayals, there have been films dealing with women’s issues. Moving away from the usual tradition, these movies have attempted to give the women central roles. Pink is one such Bollywood flick that dares to portray the contemporary issues bothering the Indian women of today. The film tries to raise such questions as: Is it unexpected of women to be modern? Don’t they have the right to say what they want to say to men? Is freedom something reserved only for men? Etc. The present paper tries to examine these questions in the backdrop of the movie.